Food safety assessment based on sodium hydrosulfite contamination in ready-to-eat and ready-to-cook food samples from various markets in Bangkok Metropolitan Region - Ngampongpun, Teerattapon; Kongthip, Kantasit; Pyungtanasup, Kanta; Udomjetjamnong, Theerada; Thanakumthorn, Ravinpat; Suracharoenchai, Sukontee; Mungmai, Supatsorn; Mungkalarungsi, Sujimon (UBRU Journal for Public Health Research, 2023)
Contamination of bleach or sodium hydrosulfide in food or food products commonly used in food preservation to inhibit the growth of microorganisms that exceeds the food sanitation standards of the Department of Health, Ministry of Public Health. Not more than 500 milligrams per 1 kilogram of food will affect consumers. This study aimed to study the situation of bleach contamination in 100 food samples from 5 types of food; noodle products, pickled bamboo shoots, fish balls, rice, and bread, 20 samples for each type. Convenient sampling methods was used to collect samples in fresh markets in Bangkok and its vicinity. The samples were tested with a bleach contamination test kit (Alert for sulfile) and the statistics used to analyze the data were descriptive statistics, i.e. number, percentage. The purpose of this study was to determine the situation of sodium hydrosulfite residue in the following foods: noodle products, pickled bamboo shoots, fish balls, rice and bread that may be harmful to consumers' health. According to food sanitation standards, Department of Health, Ministry of Public Health. The samples were collected for the study in various fresh markets in Bangkok and its vicinity. and tested with an alert for sulfite contamination test kit. The results of the analysis showed that the food samples tested were diverse and completely representative of the food groups of interest in terms of type and quantity. Sodium hydrosulphide contamination from noodle products was found. Four samples of noodles, 2 samples of rice vermicelli and 2 samples of vermicelli, were in the range of 10-100 ppm, representing 20% ​​of total noodle products. and accounted for 4 percent of all samples. From all test results, it can be concluded that examples of noodle products was found a relative high sodium hydrogen sulfite contamination. Consumers who are at risk of allergic reactions to these compounds should avoid their consumption. In addition, awareness should be raised among food manufacturers and distributors, including the cooperation of relevant personnel who have to carry out food safety inspections and improvements to reduce the risk of contamination of food additives.